2015
DOI: 10.1186/s12961-015-0032-9
|View full text |Cite
|
Sign up to set email alerts
|

An institutional approach to support the conduct and use of health policy and systems research: The Nodal Institute in the Eastern Mediterranean Region

Abstract: BackgroundThe use of health policy and systems research (HPSR) to support decision making in health systems is limited in the Eastern Mediterranean Region (EMR). This is partly due to the lack of effective initiatives to strengthen regional HPSR capacities and promote its use in decision making. This paper offers a structured reflection on the establishment and core functioning of a HPSR Nodal Institute for the EMR with specific focus on the approach used to support the conduct and use of HPSR. It seeks to gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…Findings highlight misalignment between national health research priorities and actual research production, since the majority of respondents indicated submitting proposals not addressing national health research priorities. This corroborates findings of previous studies conducted in the Region that highlighted a gap in the production of policy-relevant research (5,16,17). This can be explained by the fact that only 31.7% of the surveyed institutions reported being involved in a national priority setting exercise over the past five years.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Findings highlight misalignment between national health research priorities and actual research production, since the majority of respondents indicated submitting proposals not addressing national health research priorities. This corroborates findings of previous studies conducted in the Region that highlighted a gap in the production of policy-relevant research (5,16,17). This can be explained by the fact that only 31.7% of the surveyed institutions reported being involved in a national priority setting exercise over the past five years.…”
Section: Discussionsupporting
confidence: 90%
“…Findings also suggest that funders occasionally and rarely formulate their priorities and calls for proposals in response to national/regional needs, which can partially explain the misalignment. Respondents mostly reported NCDs as their top priority, which corresponds to regional and global priorities as declared by stakeholders, policy-makers and regional and international organizations (17,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our analysis of the characteristics of included studies provided in Additional file 3 , we note the following patterns: the years of publication ranged from 2008 to 2017, with the median year of publication being 2014; the most common jurisdictional focus of the KT platforms was country rather than sub-national, regional (supra-national) or global, while the most common country focus was Uganda (appearing in 13 studies) [ 23 , 24 , 33 , 41 48 , 52 , 53 ], Lebanon (appearing in 8 studies, of which 6 examine Lebanon in the context of the Eastern Mediterranean region) [ 28 32 , 34 , 41 , 59 ], and South Africa (appearing in 8 studies) [ 23 , 24 , 26 , 37 , 42 , 49 , 51 , 54 ]; the most common name used by the KT platforms was EVIPNet (appearing in 17 studies) [ 25 , 28 33 , 37 , 41 , 44 48 , 50 , 52 , 53 ], whether because that was the formal name of the group or because it considered itself part of the EVIPNet ‘family’ even if it went by a different name, such as REACH Policy Initiative Uganda and its variously named rapid evidence service (e.g. Makerere University’s service, REACH Policy Initiative service, SURE project service or rapid response service); the most common variables and relationships addressed, were as follows: ◦ descriptions ( n = 33 of 38 studies) [ 23 38 , 40 43 , 46 49 , 51 56 , 58 60 ] were more common than formative evaluations ( n = 18) [ 23 , ...…”
Section: Resultsmentioning
confidence: 99%
“…This also could be characterised as depicting normative dimensions of institutionalisation of knowledge use, in so much as social pressure induces individuals to behave in a particular way. This is also true for studies that were conducted at regional level [54,55,[73][74][75], which seek to develop a common understanding and establish modes of practice that can be shared across similar country contexts. For this reason, we considered these articles to illustrate both normative and cultural-cognitive types of institutionalisation.…”
Section: Institutionalisationmentioning
confidence: 99%